Two-Variables Linear System: A Smartphone-Based-E-Module with a Realistic Mathematic Education Approach - Fahmi, Syariful; Rahmawati, Rafika Yuni; Priwantoro, Soffi Widyanesti (Kreano, Jurnal Matematika Kreatif-Inovatif, 2022)
An innovative teaching material such as e-module were needed to assist students understanding the concept of mathematics. In this Research is develop an e-module using Realistic Mathematics Education approach in Linear Equation System Two Variables. Research method is using ADDIE model which consist of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The validators of this research were content and media experts, while the research subjects were students of 7th grades in Pleret Bantul Junior High School. The instruments used in data collection were interview and questionnaire. By the calculation results, the e-module was considered feasible by contents and media experts. From the validation of content expert get average of 3.56 with very good criteria, while from the media expert get 3.65 with very good criteria. The e-module was considered practical according to the students’ responses. In terms of practicality, average score of small class trial was 3.17 with good criteria, while average score of large class trial was 3.22 with good criteria. So, the average score based on content and media experts also student class trials get 3.40 with very good criteria. Therefore, smartphone-based e-module with realistic mathematics education approach on linear equation system with two variables material was feasible to use.Penelitian ini bertujuan untuk mengembangkan e-modul dengan berbasis Realistic Mathematics Education (RME) pada Sistem Persamaan Linier Dua Variabel. Metode penelitian yang digunakan adalah model ADDIE yang terdiri dari lima tahap, yaitu Analysis, Design, Development, Implementation, dan Evaluation. Validator penelitian ini yaitu ahli materi dan media serta subjek penelitian adalah peserta didik kelas VIII SMP Negeri 1 Pleret Bantul. Instrumen yang digunakan dalam pengumpulan data penelitian berupa wawancara dan angket. Berdasarkan hasil perhitungan, e-modul termasuk layak oleh ahli materi dan ahli media. Dari validasi ahli materi dan media mendapatkan kategori yang sama yaitu sangat baik dengan nilai rata-rata 3,56 dan 3,65. Berdasarkan uji kepada peserta didik e-modul termasuk praktis dengan kriteria baik pada uji coba kelas kecil dan besar dengan nilai 3,17 dan 3,22. Berdasarkan dari rata-rata gabungan ahli materi dan media serta uji coba peserta didik mencapai rata-rata skor 3,40 dengan kriteria sangat baik. Kesimpulannya e-modul berbasis smartphone dengan pendekatan Realistic Mathematics Education pada materi sistem persamaan linear dua variabel layak digunakan.